The Use of Technology at the Higher Education Level and Student Engagement: A Meta-Analysis - Ridwan Budi Pramono; Endang Retno Surjaningrum; Nono Hery Yoenanto (Universitas Ahmad Dahlan, 2023)
Student engagement is a recognized factor in higher education, and its importance in students' academic success has led to increased attention. While many studies have explored the impact of technology on student engagement, no meta-analysis studies have been conducted at the higher education level to the best of the researcher's knowledge. This study aims to critically evaluate the influence of technology on student engagement within the context of learning in Indonesia. A systematic review and assessment were conducted using seven databases and two search engines. This meta-analysis study includes 5 studies with 710 subjects. Although the 5 studies indicate that technology use can enhance student engagement, the results do not yield a common effect size. Furthermore, one study presents inconclusive findings. Therefore, further research is necessary to investigate this variable by implementing more appropriate research procedures.Keywords: technology use, meta-analysis, student engagement